AN IMPLEMENTATION OF GENRE-BASED PEDAGOGY TO TEACH EXPOSITION TEXTS ONLINE - Egi Fajriyandi, - (2023)
The mastery of text types under genre-based pedagogy gains ground in the recent English curriculum as the main learning outcomes. However, in practice, English teachers still employed other teaching methods, especially in Indonesian classrooms, as a result of their past experience. This study sought to investigate the implementation of genre-based pedagogy to teach Exposition texts by incorporating the principles of online learning. Informed by a qualitative approach, the study embraced characteristics of a case study method. The data were obtained from several sources, including teaching program which was conducted online due to the Covid-19 pandemic, student interview, and collection of samples of students' texts. The findings have shown that despite some aspects that still needed an improvement, the teaching program was successful in some ways. Most importantly, students demonstrated emerging capacity to write Exposition texts in an appropriate and effective style indicated by good control of the overall schematic structure of the texts and improved use of supporting arguments and evidence using linguistic resources typical of the target genre. It is highly suggested that the online implementation of genre-based pedagogy should explore more activities in the modelling stage of the text that can help the students learn how to provide supporting arguments in their texts realized in projecting verbal clauses more appropriately.